On the Status of Object Concepts in Aphasia - Chertkow, Howard; Bub, Daniel; Deaudon, Christine; Whitehead, Victor (Brain and language, 1997)
While verbal comprehension is often impaired in aphasia due to left hemispheric damage, the status of nonverbal conceptual knowledge of objects remains controversial. We tested 16 aphasic subjects for their comprehension of concrete single words. Eight showed significant impairment on word-to-picture matching, when distractors were semantically and not just perceptually confusable. These 8 also made errors in answering verbal probe questions concerning the same items. When tested on a nonverbal pictorial version of the same probe questions, however, 3 of these 8 improved their performance to the level of normal controls. The other 5 showed continuing impairment in indicating responses to pictorial probes. These 5 showed no evidence of generalized intellectual impairment, and it is concluded that they demonstrated a comprehension deficit not limited to the verbal domain. Unlike the other aphasic patients, these latter 5 also had CT scan lesions extending into the posterior left temporal lobe (involving Brodmann's areas 22, 21, and 37). They were also more impaired in terms of general aphasia severity. It is suggested that a nonverbal (as well as verbal) semantic memory deficit occurs in a subgroup of patients with single word comprehension disturbance due to aphasia, and this may reflect general severity of language impairment as well as damage to certain localized brain regions.